Effectiveness and tolerability of Poliprotect, a natural mucosal protective agent for gastroesophageal reflux disease and dyspepsia: Surveys from patients, physicians, and pharmacists - Cioeta, Roberto; Muti, Paola; Rigoni, Marta; Morlando, Luigi; Siragusa, Filippo; Cossu, Andrea; Giovagnoni, Emiliano (Frontiers in Drug Safety and Regulation, 2022)
Background: Gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) are very common in the general population. GERD prevalence is considerably high in pregnant women, and it increases at a young age, alongside obesity. Mucosal protective agents (MPAs) are over-the-counter (OTC) treatments for FD and GERD commonly used alone or as add-on therapy to proton pump inhibitors (PPIs). Real-world data through surveys allow a clinical evaluation of marketed products that also complies with the new regulation on substance-based medical devices (SBMDs). Aim: The study aimed to evaluate perceived effectiveness, safety, and pattern of usage among patients, physicians, and pharmacists of the natural MPA Poliprotect, as assessed by a validated survey methodology. Methods: Questionnaire repeatability was first assessed, resulting in the intraclass correlation coefficient agreement level >0.9 in the three validation cohorts of physicians, pharmacists, and patients. All questions were closed multiple-choice, allowing measuring variations in frequency, quality, or magnitude of effect on a 5-point Likert-like verbal scale. Results: Three different surveys were performed in Italy and Spain on a total of 3,471 physicians, including 77 gastroenterologists, 848 patients, and 146 pharmacists who had an experience with Poliprotect in the previous year. Over 90% of general practitioners (GPs) rated Poliprotect effectiveness as good/excellent in controlling pyrosis, 80% for epigastric pain, and approximately 70% for digestion difficulties. GPs reported Poliprotect as very or extremely useful as an alternative to PPIs (73%) and for pregnancy-associated GERD symptoms (61%), almost unanimously (99.5%) reporting an excellent to good tolerability; 79% of the gastroenterologists answered to be extremely or very satisfied with the improvement of typical GERD symptoms, whereas improvement of dyspepsia and pregnancy- and breast-feeding-associated GERD symptoms was rated as highly satisfactory for 69, 52, and 62%, respectively, among GI specialists. Its use because of painful dyspeptic symptoms was reported by over 80% of patients, who rated symptom relief as excellent/good, and reported a marked quality-of-life improvement in 73% and in 65% of their answers, respectively. The product was used as monotherapy by 63% of patients. Conclusion: Large-scale, validated surveys support the safety and effectiveness of Poliprotect in the treatment of common functional upper GI disorders.